Commodity Markets Outlook, April 2020 - World Bank Group (World Bank, Washington, DC, 2020)
Almost all commodity prices saw sharp declines during the past three months as the COVID-19 pandemic worsened. Mitigation measures have significantly reduced transport, causing an unprecedented decline in demand for oil, while weaker economic growth will further reduce overall commodity demand. Crude oil prices are expected to average $35/bbl this year and $42/bbl in 2021—sharp downward revisions from October. Metals prices are projected to drop more than 13 percent in 2020, before recovering in 2021, while food prices are expected to remain broadly stable. The price forecasts are subject to significant risks. A Special Focus looks at the impact of COVID-19 on commodity markets and finds that its effects have already been larger than most previous events and may lead to long-term shifts in global commodity markets. Another section looks at international commodity production agreements and concludes that while the current OPEC arrangement may stabilize oil markets in the short term, it will likely be subject to the same shortcomings of earlier efforts to manage commodity supplies in due course.